Pressureless glass crystallization of transparent yttrium aluminum garnet-based nanoceramics - Xiaoguang Ma (Nature Portfolio, 2018)
Transparent YAG crystals are ubiquitous in phosphors, scintillators and lasers, but are complex and costly to make. Here, the authors use a one-step pressureless crystallization of bulk glass to make a transparent biphasic YAG nanoceramic that can be doped for optical applications.